The Role of Public Service Performance Quality in Mediating Territorial Capabilities and Binter Methods on Community Satisfaction - Iskandar Iskandar; Veronika Santi Paramita (Komando (Kompetensi Manajemen dan Organisasi): Bisnis dan Pertahanan, 2024)
In accordance with the Decree of the Commander of the TNI Number Kep/1024/XII/2020 that Territorial Development (Binter) is the Main Function of the Indonesian Army in organizing the development of the potential of geography, demographics, and social conditions to become the strength of Rmoney, Alat, and Kondisi (RAK) of a formidable fight through the sterility of the TNI and the people. The existence of the TNI AD territorial command plays an important role in the defense function as well as the socio-political function that provides convenience in dealing with external and internal conflicts, ensuring the passage of law, political order and control, disaster assistance, and handling terrorism. Territorial development involving the Indonesian Army Babinsa requires competence in strategic communication, which is not only influenced by personal modalities. This research used an associative approach with quantitative method. The findings suggest that the higher the Regional Resilience, the higher the Quality of Performance and Public Services. The indirect effect of the Binter method on Community Satisfaction is 26.5%. In conclusion, by increasing Territorial Capability and Regional Resilience, Community Satisfaction with Binter will also increase.